Will future climate change increase global energy use? - Hongliang Zhang; Jianhong E. Mu; Bruce A. McCarl (University of Neuchâtel, Institute of Economic Research (IRENE), 2018)
Currently fossil-fuel-based energy accounts for 82% of global energy use and is the source of two-thirds of anthropogenic greenhouse-gas emissions (GHG). Such emissions are a primary climate change driver ultimately altering temperature and in turn influences energy use. This paper presents a global analysis of the link between energy use and temperature, along with the contributing factors of income, urbanization and population. We use an econometric model to estimate this link based on a panel dataset arising from 147 countries during 1990-2014. We find that energy use per capita has a nonlinear, convex relationship with temperature - the use initially high at low temperatures, then declining to an inflection point, and subsequently rising at high temperatures. The temperature effects on energy use per capita are not globally uniform with differences across rich and poor countries. In particular, rich countries show a larger energy use response at high temperatures than poor countries do. Projections under unmitigated climate change indicate an increase in the global, annual total energy use of 41% by 2100, relative to a baseline of no climate change. The projected increases in global total energy use are substantially larger than prior estimates from studies focused on residential energy use and may further motivate aggressive GHG mitigation and climate change adaptation.
Keywords: Q4; Q54; 330; Climate Change; Energy Use